Simple Carbohydrate Derivatives Diminish the Formation of Biofilm of the Pathogenic Yeast Candida albicans - Olena P. Ishchuk; Olov Sterner; Ulf Ellervik; Sophie Manner (MDPI AG, 2019)
The opportunistic human fungal pathogen Candida albicans relies on cell morphological transitions to develop biofilm and invade the host. In the current study, we developed new regulatory molecules, which inhibit the morphological transition of C. albicans from yeast-form cells to cells forming hyphae. These compounds, benzyl α-l-fucopyranoside and benzyl β-d-xylopyranoside, inhibit the hyphae formation and adhesion of C. albicans to a polystyrene surface, resulting in a reduced biofilm formation. The addition of cAMP to cells treated with α-l-fucopyranoside restored the yeast-hyphae switch and the biofilm level to that of the untreated control. In the β-d-xylopyranoside treated cells, the biofilm level was only partially restored by the addition of cAMP, and these cells remained mainly as yeast-form cells.